Combination of Exercise and Acupuncture Versus Acupuncture Alone for Treatment of Myofascial Pain Syndrome: A Randomized Clinical Trial - Bina Eftekharsadat; Elmira Porjafar; Fariba Eslamian; Seyed Kazem Shakouri; Hamid Reza Fadavi; Seyed Ahmad Raeissadat; Arash Babaei-Ghazani (Medical Association of Pharmacopuncture Institute, 2018)
Myofascial pain syndrome (MPS) is a common musculoskeletal disorder. This study was designed to compare the effects of aerobic exercise plus acupuncture with acupuncture alone in treatment of patients with MPS. Sixty-four patients (55 female and 9 male) with MPS in their neck and shoulders participated in the study with mean age of 33.1 ± 6.4 years. Participants were randomly allocated to aerobic exercise plus acupuncture (n = 32) or acupuncture alone (n = 32) groups. Outcome measurements included visual analog scale, pressure pain threshold, neck disability index, and quality of life that was measured with QoL-SF36 scale. Each group received 10 sessions of acupuncture in combination with aerobic exercise or acupuncture alone. The outcome measures were evaluated at baseline, at the end of the last treatment session, and at 1-month follow-up visit. While participants were waiting for their 1-month follow-up visit, the patients who received combination therapy were asked to continue their aerobic exercise by jogging 40 minutes a day. Although mean visual analog scale, pressure pain threshold, neck disability index, and QoL-SF36 were significantly improved in both groups (p < 0.001), there was no statistically significant difference among the measures between the two groups throughout the evaluated sessions. The interaction effect of time and groups did not show any significant difference among the outcome measures (p > 0.29). Keywords: acupuncture, aerobic exercise, myofascial pain syndrome, pain, trigger points